Low‐fat hypocaloric diet reduces neprilysin in overweight and obese human subjects - Henke, Christine; Haufe, Sven; Ziehl, Doreen; Bornstein, Stefan R.; Schulz‐Menger, Jeanette; Heni, Martin; Engeli, Stefan; Jordan, Jens; Birkenfeld, Andreas L. (ESC Heart Failure, 2021)
Aims Neprilysin (NEP), a zinc metallopeptidase, degrades a variety of bioactive peptides including natriuretic peptides terminating their biological action on arterial blood pressure and natriuresis. Pharmacological inhibition of NEP reduces mortality in patients with heart failure with reduced ejection fraction. Physiological interventions reducing NEP levels are unknown in humans. Because obesity leads to increased NEP levels and increases the risk for heart failure, we hypothesized that weight loss reduces NEP concentrations in plasma and tissue. Methods and results We randomized overweight to obese human subjects to a low‐fat or low‐carbohydrate hypocaloric 6 month weight loss intervention. Soluble NEP was determined in plasma, and NEP mRNA was analysed from subcutaneous adipose tissue before and after diet. Low‐fat diet‐induced weight loss reduced soluble NEP levels from 0.83 ± 0.18 to 0.72 ± 0.18 μg/L (P = 0.038), while subcutaneous adipose tissue NEP mRNA expression was reduced by both dietary interventions [21% (P = 0.0057) by low‐fat diet and 16% (P = 0.048) by low‐carbohydrate diet]. We also analysed the polymorphisms of the gene coding for NEP, rs9827586 and rs701109, known to be associated with plasma NEP levels. For both single‐nucleotide polymorphisms, minor allele carriers (A/A) had higher baseline plasma NEP levels (rs9827586: β = 0.53 ± 0.23, P < 0.0001; rs701109: β = 0.43 ± 0.22, P = 0.0016), and minor allele carriers of rs9827586 responded to weight loss with a larger NEP reduction (rs9827586: P = 0.0048). Conclusions Our study identifies weight loss via a hypocaloric low‐fat diet as the first physiological intervention in humans to reduce NEP in plasma and adipose tissue. Specific single‐nucleotide polymorphisms further contribute to the decrease. Our findings may help to explain the beneficial effect of weight loss on cardiac function in patients with heart failure.